Atherogenicity of diabetic rats administered single and combinatorial herbal extracts - Chinwendu M. Chikezie; Okey A. Ojiako; Adamma A. Emejulu; Paul C. Chikezie (Faculty of Pharmacy, Cairo University, 2018)
Objective: The present study sought to investigate atherogenicity of alloxan-induced diabetic rats administered single and combinatorial herbal formulations of Acanthus montanus, Asystasia gangetica, Gongronema latifolium and Solanum melongena. Methods: A single intra-peritoneal (i.p.) injection of 90 mg/kg b.w. of alloxan monohydrate was given to the rats to induce diabetes mellitus (DM). Serum lipid profiles were measured using standard spectrophotometric methods, whereas atherogenicity, serum lipid ratios and atherogenic coefficient/indices were calculated using standard formulae. Results: Serum total cholesterol (TC) concentrations of experimental rat groups varied between 1.59 ± 0.10 mmol/L and 2.72 ± 0.16 mmol/L (p < 0.05). Serum high-density lipoprotein cholesterol (HDL-C) concentration of untreated DM rat (DM-r) group was significantly lower (p < 0.05) than those of treated DM-r groups. Atherogenic risk indices (ARIs) of treated DM-r groups were within the range of 0.74 ± 0.03 and 2.64 ± 0.21, whereas ARI of untreated DM-r was 4.04 ± 0.25. The linear regression analysis of atherognic index of plasma (AIP) versus serum low-density lipoprotein cholesterol (LDL-C) concentrations of the experimental rat groups gave a relatively close fitted regression line (R2 = 0.8275). Atherogenic protection of herbal extract treated DM-r groups was within the range of 33.4-81.7%. Conclusion: The present study showed that double herbal formulations (DHFs): A. gangetica + G. latifolium and A. gangetica + A. montanus offered comparatively high protection to DM-r against atherogenic outcomes, which paralleled the capacities of these DHFs to reverse dyslipidemia. Keywords: Atherogenicity, Diabetes mellitus, Dyslipidemia, Herbal, Serum lipid profile